Download presentation

1
**Exponents and Polynomials**

2
**Chapter Sections 4.1 – Exponents 4.2 – Negative Exponents**

4.3 – Scientific Notation 4.4 – Addition and Subtraction of Polynomials 4.5 – Multiplication of Polynomials 4.6 – Division of Polynomials Chapter 1 Outline

3
**Multiplication of Polynomials**

4
**Multiplying Polynomials**

To multiply two monomials, multiply the coefficients and use the product rule of exponents. Example: (7x3)(6x5) = 7 · x36 · 6 · x5 = 42x8 To multiply a polynomial by a monomial, use the distributive property: a(b + c) = ab + ac Example: Multiply 3x(2x2 + 4) 3x(2x2 + 4) = (3x)(2x2) + (3x)(4) = 6x3 + 12x

5
**Multiplying Polynomials**

To multiply two binomials, use the distributive property so every term in one polynomial is multiplied by every term in the other polynomial. Example: a.) (x + 3)(x + 4) = (x + 3)(x) + (x + 3)(4) = x2 + 3x + 4x + 12 = x2 + 7x + 12 A common method used to multiply two binomials is the FOIL method.

6
**The FOIL Method F O I L Consider (a + b)(c + d):**

Stands for the first – multiply the first terms together. (a + b) (c + d): product ac Stands for the outer – multiply the outer terms together. (a + b) (c + d): product ad O Stands for the inner – multiply the inner terms together. (a + b) (c + d): product bc I Stands for the last – multiply the last terms together. L (a + b) (c + d): product bd The product of the two binomials is the sum of these four products: (a + b)(c + d) = ac + ad + bc + bd

7
**The FOIL Method Using the FOIL method, multiply (2x - 3)(x + 4) .**

+ (-3)(4) L = (2x)(x) (2x - 3) (x + 4) F + (-3)(x) I O + (2x)(4) = 2x x x = 2x 2 + 5x - 12

8
**Formulas for Special Products**

Product of the Sum and Difference of the Same Two Terms (a + b)(a – b) = a2 – b2 The expression on the right side of the equals sign is called the difference of two squares. Example: a.) (x + 5) (x – ) = x2 - 25

9
**Formulas for Special Products**

Square of Binomials (a + b)2 = (a + b)(a + b) = a2 + 2ab + b2 (a – b)2 = (a – b)(a – b) = a2 – 2ab + b2 To square a binomial, add the square of the first term, twice the product of the terms and the square of the second term. Example: a.) (x + 5)2 = (x)2 + 2(x)(5) + (5)2 = x2 + 10x + 25

Similar presentations

© 2020 SlidePlayer.com Inc.

All rights reserved.

To make this website work, we log user data and share it with processors. To use this website, you must agree to our Privacy Policy, including cookie policy.

Ads by Google